Ragtime : the musical : original Broadway cast recording [compact disc] - Flaherty, Stephen; Flaherty, Stephen (Concord Theatricals Corp. ; Lincoln Center Theater, 2026)
Ragtime follows three fictional families pursuing the American Dream at the dawn of the 20th century: a black pianist and his beloved, a Jewish immigrant and his little girl, and a wealthy white family. Featuring a lush score by Tony Award winners Stephen Flaherty and Lynn Ahrens, and starring Joshua Henry, Caissie Levy, and Brandon Uranowitz, Ragtime weaves a rich tapestry that blurs the line between personal struggle and national identity.